ASSESSMENT OF THE HYDROPOWER POTENTIAL OF SMALL RIVERS IN UKRAINE USING MODERN MEASUREMENT SYSTEMS - Ващишак, Ірина; Чернецька, Ірина (SWorldJournal, 2026)
The article addresses the актуal problem of assessing the hydropower potential of small rivers in Ukraine in the context of renewable energy development and improving the energy efficiency of decentralized power systems. The feasibility of utilizing small